2006
DOI: 10.1111/j.1365-3040.2006.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous supply of glutamine and active cytokinin to the roots reduces NO3uptake rates in poplar

Abstract: The present study shows for the first time the influence of exogenously applied amino acids and cytokinin on the physiological and molecular aspects of N metabolism in poplar trees. In a short-term feeding experiment, glutamine or trans-zeatin riboside ( t ZR) was added directly to the nutrient solution. NO 3 -net uptake declined significantly in response to both treatments. Feeding with glutamine brought about an increase in concentrations of different amino compounds in the roots (glutamine, glutamate, alani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 66 publications
1
27
0
1
Order By: Relevance
“…This accumulation seems to result in a repression of nitrate uptake at the transcriptional or post-transcriptional level [72][73][74]. However, the mechanism(s) of how trees sense whole plant N status and transmit this information into changes in root uptake remain poorly understood.…”
Section: Regulation Of N Acquisition and Distribution In Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…This accumulation seems to result in a repression of nitrate uptake at the transcriptional or post-transcriptional level [72][73][74]. However, the mechanism(s) of how trees sense whole plant N status and transmit this information into changes in root uptake remain poorly understood.…”
Section: Regulation Of N Acquisition and Distribution In Treesmentioning
confidence: 99%
“…The release of repression of the transcription of nitrate transporters also requires a systemic signal communicating that whole plant N demand for actual growth and development exceeds N acquisition by the roots. It has been suggested that a cycling pool of cytokinins mediates such a feed-forward control in trees [73,74] and that the concerted action of feedback control by cycling glutamine and feed-forward control by cycling cytokinins regulate nitrate acquisition at the whole plant level [54,81]. However, this assumption requires further research using trees with different N nutritional states.…”
Section: Regulation Of N Acquisition and Distribution In Treesmentioning
confidence: 99%
“…Also, synthesis of cytokinins depends on the availability of different macronutrients: cytokinin contents are increased by nitrate supply (Takei et al, 2001;Collier et al, 2003), and decreased by N or P starvation (Salama and Wareing, 1979;Horgan and Wareing, 1980). Finally, applications of exogenous cytokinin were shown to repress the expression of transporters involved in sulfate, nitrate, or phosphate uptake and to reduce the net nitrate uptake (Martín et al, 2000;Maruyama-Nakashita et al, 2004b;Brenner et al, 2005;Dluzniewska et al, 2006). It has been well demonstrated that cytokinins significantly down-regulate SULTR1.1 and SULTR1.2 with major impact on the latter; however, it should be noted that this negative effect is independent of the S limitation response (Maruyama-Nakashita et al, 2004c).…”
Section: Sultr12 and Sulfate Content In Rootsmentioning
confidence: 99%
“…Assimilation of ammonium into glutamine is mediated by glutamine synthetase enzyme. Glutamate synthase converts glutamine into two glutamate molecules (Glutamine and glutamates are used for synthesis of other amino acids [255] [256].…”
Section: Translocation and Assimilation Of Ammoniummentioning
confidence: 99%
“…Nitrogen uptake is controlled by many factors, such as nitrogen level, energy status of the plant, assimilation status of imported nitrogen, nitrogen demand, and involves mobile signals between shoots and roots as well as between different parts of the root system [369]. [372]. Both exogenous supply and internal increase of amino acids inhibit expression of nitrate transporters and nitrate uptake while decrease in level of root amino acids stimulated uptake of nitrogen [234] [373] [374].…”
Section: Regulation Of Nitrogen Uptakementioning
confidence: 99%